Quantum dynamics and tunnelling of methyl rotors studied by field-cycling NMR - Sun, Cheng (2009)
Quantum dynamics and tunnelling of methyl rotors has been studied using field-cycling nuclear magnetic resonance (NMR) spectrometer, in a variety of samples. The characteristic frequency of the tunnelling motion of methyl groups has been investigated using both low-field dipole-dipole driven experiments and tunnel resonance level-crossing experiments. The classical hopping and quantum tunnelling of methyl groups have been studied by making temperature-dependent and field-dependent measurements of the spin-lattice relaxation time T1. The spectral density functions of the dipolar interaction, mediated by the rotation of methyl groups, have been directly plotted, and the correlation times characteristic of the rotational motion have been determined.